2016
DOI: 10.1021/acsnano.6b03863
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Ligand-Mediated Synthesis of Colloidal CsPbBr3 Perovskite Nanocrystals: The Role of Organic Acid, Base, and Cesium Precursors

Abstract: While convenient solution-based procedures have been realized for the synthesis of colloidal perovskite nanocrystals, the impact of surfactant ligands on the shape, size, and surface properties still remains poorly understood, which calls for a more detailed structure-morphology study. Herein we have systematically varied the hydrocarbon chain composition of carboxylic acids and amines to investigate the surface chemistry and the independent impact of acid and amine on the size and shape of perovskite nanocrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
882
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 779 publications
(922 citation statements)
references
References 44 publications
39
882
0
1
Order By: Relevance
“…12,16,17 The size and shape of the particles are important factors determining the resulting optical properties because of their influence on the bandgap, known as the quantum size effect. 18,19 CsPbX 3 nanocrystals are frequently synthesized in the form of nanocubes, while two-dimensional morphologies such as nanosheets and nanoplatelets are also obtained.…”
Section: Influence Of Organic Ligands On Particle Morphologies Of Cspmentioning
confidence: 99%
See 1 more Smart Citation
“…12,16,17 The size and shape of the particles are important factors determining the resulting optical properties because of their influence on the bandgap, known as the quantum size effect. 18,19 CsPbX 3 nanocrystals are frequently synthesized in the form of nanocubes, while two-dimensional morphologies such as nanosheets and nanoplatelets are also obtained.…”
Section: Influence Of Organic Ligands On Particle Morphologies Of Cspmentioning
confidence: 99%
“…Pan et al reported the dependence of the particle morphology on the synthesis temperature and the length of the n-alkyl carboxylic acids and n-alkylamines used in the hot-injection method, as summarized in Figure 5. 12 When the synthesis was performed at 170…”
Section: Influence Of Organic Ligands On Particle Morphologies Of Cspmentioning
confidence: 99%
“…To avoid the solubility-related issues, cesium acetate (CsOAc) was also used as the cesium source. 47 During heating, the formation of a cesium-oleate complex occurs in the flask and this complex is finally converted into CsPbX 3 QDs when it is injected into the source of PbX 2 with OLAM/OLA/1-ODE. It was reported by the authors that the mixture of oleylamine/oleic acid (OLAM/OLA) with 1-ODE helps to solubilize the PbX 2 salt.…”
Section: Introductionmentioning
confidence: 99%
“…48 The presence of the alkyl ammonium ion on the surface was also confirmed through H 1 NMR spectroscopy. 47 The final morphology of the QDs obtained in the reaction can be varied by simply playing with the addition of new solvents and ligands. Indeed, this solvent chemistry helped to obtain a nanosheets (NSs) structure of Cs-LHQDs, which is normally a complicated one due to its cubic structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation